Clinical spectral characterisation of colonic mucosal lesions using autofluorescence and δ aminolevulinic acid sensitisation. Issue 4 (1st April 1999) - Eker, C; Montán, S; Jaramillo, E; Koizumi, K; Rubio, C; Andersson-Engels, S; Svanberg, K; Svanberg, S; Slezak, P
Abstract : BACKGROUND AND AIMS: Laser induced fluorescence (LIF) from colonic mucosa was measured in vivo with and without δ aminolevulinic acid (ALA) in an attempt to differentiate between neoplasia and non-neoplasia in real time during colonoscopy. METHODS: Spectra from 32 adenomas, 68 normal sites, and 14 hyperplastic polyps in 41 patients were obtained with a point monitoring system. Twenty one of the patients had been given a low dose of ALA as a photosensitiser before the examination. Light of 337, 405, or 436 nm wavelength was used as excitation. Stepwise multivariate linear regression analysis was performed. RESULTS: With 337 nm excitation, 100% sensitivity and 96% specificity was obtained between normal mucosa and adenomas. Seventy seven per cent of the hyperplastic polyps were classified as non-neoplastic. When exciting with 405 and 436 nm, the possibility of distinguishing different types of tissue was considerably better in the ALA patients than in the non-ALA patients. CONCLUSIONS: The in vivo point measurements imply that a good discrimination between normal tissue and adenomatous polyps can be obtained using the LIF technique. Excitation at 337 nm and at 405 nm or 436 nm using ALA gives good results. LIF also shows potential for distinguishing adenomatous from hyperplastic polyps. The number of detection wavelengths could be reduced if chosen properly.